The educational aspects inferred from the rights of the trustees in Islamic jurisprudence - Alnemasi, Bader Jazza Naif (Journal of Educational and Psychological Sciences, 2023)
The purpose of the study to find out who is insured and who is called in Islamic jurisprudence? Learn about the educational aspects Guaranteed by Islam for the insured. The researcher used the deductive and analytical method. To study and analyze texts. and extract the educational principles contained therein.The results of the study showed Observance of Islamic Sharia, spiritual aspects and the psychological, social and educational rights of the insured. This confirms the greatness of Islamic law in preserving the rights of individuals in a society.
Keywords: The insured; educational aspects in the rights of the insured